Assessing the Papuan Government’s Policy for Tackling the Spread of Coronavirus (COVID-19) - Johni R. V. Korwa; Diego R. De Fretes; Meyland S. F. Wambrauw; Jackson Yumame; Christine O. I. Sanggenafa; Reni Shintasari; Ferinandus L. Snanfi (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2020)
This paper aims to assess the Papuan government’s policy for preventing the spread of COVID-19 through the shutdown of travel to the region based on the Papua joint statement. Excluding the transportation of goods, Papua was the first province in Indonesia to restrict entry into the region by both sea and air travel. To analyse the Papuan government’s policy, Edwards’ theory of policy implementation was adopted. Using first-hand interviews, observations, and library research, this paper argues that the government of Papua has made the right decision to close its borders, despite challenges, as part of a strict policy to protect the region from COVID-19. It is also worth noting that although five regions selected for this study (Jayapura City, Mimika, Biak Numfor, Merauke and Yapen Regency) reflected variations between one another in policy implementation, they all had expressed how the local government in Papua was doing the best they could to eradicate COVID-19. The use of theoretical frameworks (communication, resources, dispositions, and bureaucratic structures) as part of policy implementation had also been effective, despite that some parts need to be improved. The results of this study include recommendations for effective coordination among policymakers, the availability of laboratory testing, adoption of evidence-based policies and improving the health system in Papua.